Pollution Abatement of Devika and Tawi River at Udhampur Town (International Journal of Innovative Research in Computer Science & Technology, 2022)
In India, rapid industrialization & socio economic adjustments have caused an accelerated urban  boom. However, up-gradation & implementation of the  vital infrastructure has no longer kept tempo with the  developing urban population. The result has been extreme  pollutants of the rivers, as both untreated or partially  treated sewage is being discharged into the water  resources & affects the lifelines of humans of the town.  At River Devika water excellent is poor for consumption  and bathing requirements. Silt deposition is a  fundamental issue together with the river being flooded  with waste materials, excessive BOD and COD are  recorded, the holy dip is sort of impossible so people are  concerned about these shabby conditions. Tawi River is  the main river of Udhampur city originating from  Bhaderwah and walking due north to south, passing with  the aid of the town Udhampur. The falling ecological  health of the Tawi is a major concern nowadays. GIS is  now an efficient and affordable planning information  system. It is fetching an essential part of the preparation  support system. The sanitation system not only deals with  environmental issues but here also talks to religious  advocates throughout the city, many religious activities are carried out in the Holy River Devika area. It is not at  all easy to evaluate the benefits of providing a proper  sanitation system and waste disposal systems in public  health, the importance of which is well known.
Keywords: Water Quality; Water Quality Analysis; Udhampur; Jammu; GIS; Tawi River